1980
DOI: 10.1128/aac.18.5.789
|View full text |Cite
|
Sign up to set email alerts
|

Penicillinase-producing Neisseria gonorrhoeae in the Netherlands: epidemiology and genetic and molecular characterization of their plasmids

Abstract: Penicillinase-producing Neisseria gonorrhoeae strains were isolated in the Netherlands with increasing frequency during the period of 1976 to 1979. About 3% of the gonococci isolated in the first half of 1979 produced penicillinase. In contrast to the period of 1976 to 1977, most penicillinase-producing N. gonorrhoeae infections during the period of 1978 to 1979 were contracted in the Netherlands. The results of genetic and molecular studies on 80 penicillinaseproducing N. gonorrhoeae strains were similar to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0
2

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
4
18
0
2
Order By: Relevance
“…All 3-lactamaseproducing strains harbored a plasmid (pLQ920) of 3.7 megadaltons (MDa), along with smaller plasmids of molecular sizes between 0.75 and 2.2 MDa. The presence of cryptic plasmids of less than 2.0 MDa was previously observed in H. parainfluenzae (2,11,17,20). Plasmid DNA purification by cesium chloride-ethidium bromide gradients (10) yielded the same patterns of bands (Fig.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…All 3-lactamaseproducing strains harbored a plasmid (pLQ920) of 3.7 megadaltons (MDa), along with smaller plasmids of molecular sizes between 0.75 and 2.2 MDa. The presence of cryptic plasmids of less than 2.0 MDa was previously observed in H. parainfluenzae (2,11,17,20). Plasmid DNA purification by cesium chloride-ethidium bromide gradients (10) yielded the same patterns of bands (Fig.…”
supporting
confidence: 56%
“…Usually considered a component of the normal flora of the upper respiratory tract, H. parainfluenzae is less commonly encountered as a urogenital commensal but has nevertheless been considered to be a causative agent of urethritis in humans (3, 5,19). Rarely, P-lactamase-producing H. parainfluenzae has been isolated from genital specimens (19,20 harbored Haemophilus spp. in the anogenital area, and three strains, 11, 259, and 361, were found, by hydrolysis of the chromogenic cephalosporin nitrocefin (Oxoid Ltd., Basingstoke, England), to produce P-lactamase.…”
mentioning
confidence: 99%
“…The isoelectric point obtained was 5.4, which suggests that this ß-lactamase isolated from N. gonorrhoeae belongs to the TEM-1 type (Van Embden et al 1980). Percival et al (1977) and Phillips (1976) found similar results in other Neisseria strains.…”
Section: Resultsmentioning
confidence: 88%
“…The 10.5-MDa plasmid is of an unusual size which has not been described previously for a plasmid in N gonorrhoeae. Atypical plasmids of 7.5 and 7.8 MDa have been shown to occur in strains of N. gonorrhoeae [25,26]. Johnson et al [25] have demonstrated that these plasmids are composed of directly repeated copies of the 2.6-MDa cryptic plasmids which can be highly unstable [27].…”
Section: Discussionmentioning
confidence: 99%